Massive In Vitro Propagation of Sandalwood Through Friable Embryogenic Callus - Supatmi, Supatmi; Ardiyanti, Nurdiya; Rahman, Nurhamidar; Sudarmonowati, Enny (BRIN, 2016)
Sandalwood (Santalum album), which belongs to Santalaceae family, is a commercially important tree in Indonesia due to its essential oil contents used for important essence of perfume in the perfumery industry. However, its population has significantly depleted since the planting materials of this tree using conventional methods are difficult to be provided. This study was conducted to mass propagate sandalwood using in vitro methods through friable embryogenic callus (FEC). The somatic embryos were formed using leaves in length of 1-3 and 4-7 mm cultured in MS medium containing 0.5 mg/l and 1 mg/l indole acetic acid (IAA), MS medium supplemented with 1 mg/l IAA and 0.2 mg/l kinetin and half concentration of MS medium supplemented with 1 mg/l Gibberellic acid (GA3). Primary somatic embryos (PSE) and secondary somatic embryos (SSE) then formed friable embryogenic callus when it repetitively transferred into MS medium supplemented with 1.7 mg/l BAP, 1 mg/l proline or 1.5 mg/l BAP and 1.2 mg/l kinetin every 3 weeks. The FEC shows its optimum maturation and regeneration in the MS medium supplemented with 1.5 mg/l BAP and 1.2 mg/l kinetin for 4-8 weeks. The acclimatization of sandalwood plantlets were perfectly conducted in the medium containing soil, sand and compos in ratio of 1:1:1 with the companion plant namely Murraya paniculata, (L) Jack which gave the best percentage of survival rate and the lowest percentage of fallen leaves. These findings may improve the massive propagation of sandalwood through FEC as well as a useful material for further genetic improvement of sandalwood by using FEC as material for genetic transformation.